Multiple factors contribute to bimodal toxin gene expression in Clostridioides (Clostridium) difficile. Issue 4 (14th October 2018) - Ransom, Eric M.; Kaus, Gabriela M.; Tran, Phuong M.; Ellermeier, Craig D.; Weiss, David S.
Summary: Clostridioides (formerly Clostridium ) difficile produces two major toxins, TcdA and TcdB, upon entry into stationary phase. Transcription of tcdA and tcdB requires the specialized sigma factor, σ TcdR, which also directs RNA Polymerase to transcribe tcdR itself. We fused a gene for a red fluorescent protein to the tcdA promoter to study toxin gene expression at the level of individual C. difficile cells. Surprisingly, only a subset of cells became red fluorescent upon entry into stationary phase. Breaking the positive feedback loop that controls σ TcdR production by engineering cells to express tcdR from a tetracycline‐inducible promoter resulted in uniform fluorescence across the population. Experiments with two regulators of tcdR expression, σ D and CodY, revealed neither is required for bimodal toxin gene expression. However, σ D biased cells toward the Toxin‐ON state, while CodY biased cells toward the Toxin‐OFF state. Finally, toxin gene expression was observed in sporulating cells. We conclude that (i) toxin production is regulated by a bistable switch governed by σ TcdR, which only accumulates to high enough levels to trigger toxin gene expression in a subset of cells, and (ii) toxin production and sporulation are not mutually exclusive developmental programs. Abstract : Clostridioides difficile, the leading cause of antibiotic‐associated diarrhea, produces toxins that inactivate host Rho GTPases. We used a fluorescent reporter to visualize toxin gene expression in C. difficile within individual cells. Our findings imply toxin production is an example of bistability governed by cell‐to‐cell variation in the levels of the sigma factor TcdR, which is directly required for transcription of the toxin genes. TcdR levels are in turn controlled by several metabolic and genetic inputs.